Theoretical and infrared spectroscopy study of the structure of copper(II) poly-5-vinyltetrazolate and the products of its thermolysis - Matulis, Vitaly E.; Ragoyja, Ekaterina G.; Zuraev, Alexander V.; Grigoriev, Yuri V.; Ivashkevich, Oleg A. (Journal of the Belarusian State University. Chemistry, 2020)
The structure of copper(II) poly-5-vinyltetrazolate and the products of its thermolysis has been studied by means of density functional theory and infrared spectroscopy. Copper(II) poly-5-vinyltetrazolate has been obtained and subsequently subjected to thermolysis. Infrared spectra of copper(II) poly-5-vinyltetrazolate and the products of its thermolysis have been recorded. The possible ways of coordination of copper(II) ions with tetrazole-containing ligands were established by analyzing the calculated molecular electrostatic potential distribution and comparing the calculated IR-spectra of the model structures to the experimental ones. It has been shown that the best agreement between the calculated and experimental data is observed for the model with three-coordinated copper(II) ions, which includes both the tetrazole-containing ligands coordinating two copper(II) ions through N(1)- and N(3)-atoms of the tetrazole ring, and the tetrazolecontaining ligands coordinating one copper(II) ion through either the N(2)- or the N(3)-atom. Recently we have shown that the product of thermolysis of copper(II) poly-5-vinyltetrazolate exhibits high catalytic activity in homocoupling of phenylacetylene and Huisgen [3 + 2]-cycloaddition. To establish the structure of the products of thermolysis of copper(II) poly-5-vinyltetrazolate, seven possible products have been proposed based on the analysis of the structure of copper(II) poly-5-vinyltetrazolate and the experimental IR-spectrum. IR-spectra of all proposed products have been calculated and the results of the calculations have been compared with the experimental IR-spectrum of copper(II) poly-5-vinyltetrazolate thermolysis product. It has been shown that the main product of thermolysis is cis-polycyanoacetylene.